Mineralogy of Tailings: Challenges to Usual Routines of Characterization - U. Kelm; L. Gutiérrez; O. Jerez; J. Morales; A. Novoselov (International Mineral Processing Congress, 2018)
"In Chile, the evaluation to reprocess tailings for elements other than the traditional Cu, Mo, Au, and Ag, as well as projects to implement long-term monitoring of mining residue sites are key elements of the government’s roadmap laid out for the mining industry for the next two decades. Characterization routines for tailings and mining residues in general have to be adapted from traditional ore and gangue mineral and micro-chemical studies. This contribution summarizes key aspects for the regional mining industry for a basic characterization of tailings with emphasis on small- to medium-size operations with limited in-house facilities and funds to carry out extensive characterization programs. The oldest tailings in Chile were deposited almost a century ago; this fact gives importance to the recovery of past ore /gangue feed information, process circuits and changes (e.g. acid to alkaline flotation), process water provenance and recovery, meteorological registers, and routines of filling a tailings impoundment. Basic characterization should include X-ray fluorescence spectrometry combined with laser diffraction (LD) granulometry followed by X-ray diffraction (XRD), optical microscopy (OM) and automated mineral analysis (AMA) on a reduced set of samples identified by hierarchical cluster analysis. For this detailed stage, only coarse tailings are recommended for direct a study by microscopy and automated mineralogy (P80 >100 µm); for fine tailings (P80 ~30 µm) a combination of XRD and deposit type adapted sequential extraction are more informative options. In particular, for XRD of clay phases, losses of crystallinity may result in deviation of spectra from standard reference phases due to prolonged storage. To monitor surface alteration, scanning electron microscopy can be complemented by Raman spectroscopy to detect residual reagents on mineral surfaces. For reactivity modeling BET measurements are essential."